Food security and nutritional status of children under-five in households affected by HIV and AIDS in Kiandutu informal settlement, Kiambu County, Kenya. Issue 1 (December 2016) - Chege, Peter; Ndungu, Zipporah; Gitonga, Betty
Abstract Background HIV and AIDS affect most the productive people, leading to reduced capacity to either produce food or generate income. Children under-fives are the most vulnerable group in the affected households. There exists minimal information on food security status and its effect on nutritional status of children under-fives in households affected by HIV and AIDS. The aim of this study was to assess food security and nutritional status of children under-five in households affected by HIV and AIDS in Kiandutu informal settlement, Kiambu County. Methods A cross-sectional analytical design was used. A formula by Fisher was used to calculate the desired sample size of 286. Systematic random sampling was used to select the children from a list of identified households affected by HIV. A questionnaire was used to collect data. Focus group discussion (FGD) guides were used to collect qualitative data. Nutri-survey software was used for analysis of nutrient intake while ENA for SMART software for nutritional status. Data were analyzed using SPSS computer software for frequency and means. Qualitative data was coded and summarized to capture the emerging themes Results and discussion Results show that HIV affected the occupation of people with majority being casual laborers (37.3 %), thus affecting the engagement in high income generating activities. Pearson correlation coefficient showed a significant relationship between dietary diversity score and energy intake (r  = 0.54p  = 0.044) and intake of vitamin A, iron, and zinc (p  < 0.05). A significant relationship was also noted on energy intake and nutritional status (r  = 0.78p  = 0.038). Results from FGD noted that HIV status affected the occupation due to stigma and frequent episodes of illness. The main source of food was purchasing (52.7 %). With majority (54.1 %) of the households earning a monthly income less than US$ 65, and most of the income (25.7 %) being used for medication, there was food insecurity as indicated by a mean household dietary diversity score of 3.4 ± 0.2. This together with less number of meals per day (3.26 ± 0.07 SD) led to consumption of inadequate nutrients by 11.4, 73.9, 67.7, and 49.2 % for energy, vitamin A, iron, and zinc, respectively. This resulted to poor nutritional status noted by a prevalence of 9.9 % in wasting. Stunting and underweight was 17.5 and 5.5 %, respectively. Qualitative data shows that the stigma due to HIV affected the occupation and ability to earn income. Conclusions The research recommends a food-based intervention program among the already malnourished children.